O1 Serogroup Cholera Vibrios Isolated from the Rostov-on-Don Water Bodies in the Course of Surveillance in 2008–2012 - M. I. Ezhova; V. D. Kruglikov; A. S. Vodop’Yanov; S. O. Vodop’Yanov; I. S. Shestialtynova; I. P. Oleynikov; N. B. Nepomnyashchaya; O. A. Podoynitsyna (Проблемы особо опасных инфекций, 2013)
Identified are the peculiarities of biological properties and origin of cholera vibrio O1 serogroup strains isolated from the Rostov-on-Don water bodies in the course of surveillance in 2008–2012. 41 atoxigenic V. cholerae O1 strains have been isolated from 767 water samples and investigated. Stable tendency of isolation of increased numbers of atoxigenic V. cholerae O1 strains over time has been demonstrated. In addition, in the strains under study detected have been the genes of additional pathogenicity factors, by PCR genotyping using specific primers for 45 nucleotide sequences associated with V. cholerae pathogenicity. The strains have also been classified according to 19 VNTR-genotypes grouped into 6 clusters based on VNTR-typing using exclusive copyright locus-specific primers. Discovered have been the strains with similar genotypes though isolated at different points both throughout the year and over the period of several years. These ones have probably been imported. They are characterized by a capacity to persist in ambient water bodies for a certain period of time.